Respuesta :
Answer:
0
Step-by-step explanation:
Simplify each expression.
a²b-31²2 a²b²
a=0,b=0
0^2 - 31^2 * 0^2 * 0^2=
-31^2*0=
961 * 0 =
0
Answer:
[tex]\sf a^2b-31^22 a^2b^2[/tex] When, [tex]\sf a=0, b=0[/tex]
We'll substitute a with 0 and b with 0.
[tex]\sf \left(0\right)^2\left(0\right)-31^22\left(0\right)^2\left(0\right)^2[/tex]
Calculate the exponents.
[tex]\sf 0 \times\left(0\right)-31^2\times\:2\left(0\right)^2\left(0\right)^2[/tex]
[tex]\sf 0\times\left(0\right)-961\times\:2\left(0\right)^2\left(0\right)^2[/tex]
[tex]\sf 0\times\left(0\right)-961\times\:2\times \:0\times \left(0\right)^2[/tex]
[tex]\sf 0\times\left(0\right)-961\times\:2\times\:0\times\:0[/tex]
[tex]\sf 0-961\times\:2\times\:0\times\:0[/tex]
[tex]\sf 0-0[/tex]
[tex]\sf 0[/tex]
____________________________